2021
DOI: 10.1186/s12913-021-06398-0
|View full text |Cite
|
Sign up to set email alerts
|

Health system determinants of tuberculosis mortality in South Africa: a causal loop model

Abstract: Background Tuberculosis (TB) is a major public health concern in South Africa and TB-related mortality remains unacceptably high. Numerous clinical studies have examined the direct causes of TB-related mortality, but its wider, systemic drivers are less well understood. Applying systems thinking, we aimed to identify factors underlying TB mortality in South Africa and describe their relationships. At a meeting organised by the ‘Optimising TB Treatment Outcomes’ task team of the National TB Thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 59 publications
1
23
0
1
Order By: Relevance
“…In Sub-Saharan Africa (SSA), declining rates of extreme poverty [1,2] have been accompanied by increasing rates of non-communicable diseases (NCDs) [3][4][5][6][7], persistent burdens of infectious disease [8][9][10][11][12], and emerging pathogens such as the novel coronavirus (COVID-19) [13]. Given the magnitude of the epidemics of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) and tuberculosis (TB), targeted resources have come from donor nations, the U.S. President's Emergency Plan for AIDS Relief (PEPFAR), the Global Fund to Fight AIDS, Tuberculosis and Malaria (Global Fund), and ministries of health to scale-up testing and treatment [14].…”
Section: Introductionmentioning
confidence: 99%
“…In Sub-Saharan Africa (SSA), declining rates of extreme poverty [1,2] have been accompanied by increasing rates of non-communicable diseases (NCDs) [3][4][5][6][7], persistent burdens of infectious disease [8][9][10][11][12], and emerging pathogens such as the novel coronavirus (COVID-19) [13]. Given the magnitude of the epidemics of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) and tuberculosis (TB), targeted resources have come from donor nations, the U.S. President's Emergency Plan for AIDS Relief (PEPFAR), the Global Fund to Fight AIDS, Tuberculosis and Malaria (Global Fund), and ministries of health to scale-up testing and treatment [14].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of research aims found in the 23 articles, four themes emerged: 1) to examine the complexity of a public health topic and illustrate complex systems thinking [26][27][28][29][30][31][32][33][34]; 2) to discuss the complexity of a public health intervention [35][36][37][38][39][40]; 3) to describe study protocol and how CLDs were created [41][42][43][44]; and 4) to illustrate how CLDs can be used to monitor and track initiatives to improve population health or evaluate impact of interventions [45][46][47][48].…”
Section: Research Aimsmentioning
confidence: 99%
“…Both primary and secondary data were used for creating CLDs (Table 3). Most articles reported on primary data collection (18/ 23) and this included interviews [26,27,33,[35][36][37][38][39][40], group model building with stakeholders and/or community members [32,41,43,44,46,48], behavioral data [42,47], fieldnotes [37], and workshops with experts [31]. Twelve articles used primary data only.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations